A dynamic paging scheme for long‐term evolution mobility management. Issue 4 (2nd April 2013) - Lin, Yi‐Bing; Liou, Ren‐Huang; Chang, Chun‐Ting
Abstract In long‐term evolution, the service area is partitioned into several tracking areas (TAs), which comprise one or more cells (the radio coverages of base stations). The TAs are grouped into TA list (TAL). When an incoming call arrives, the network attempts to connect to the user equipment (UE) by paging the cells in the UE's TAL, which may incur large paging traffic that significantly consumes the limited radio resources. To resolve this issue, this paper proposes a dynamic paging scheme that determines the paging sequence of cells in real time according to the UE movement and call behavior. We compare the performance of the dynamic paging with that of the previously proposed Cell‐TA‐TAL (CTT) paging. Our study indicates that the dynamic paging outperforms the CTT paging when movement pattern is regular and the UE moves frequently. Copyright © 2013 John Wiley & Sons, Ltd.